2015
DOI: 10.4067/s0717-66432015000200003
|View full text |Cite
|
Sign up to set email alerts
|

Compositional patterns of ruderal herbs in Santiago, Chile

Abstract: Fragmentation of the natural environment is a consequence of urbanisation. It impacts the biodiversity of native flora that characterises a region. This study focused on characterising the diversity, composition and distribution of native and alien ruderal species present in different suburbs of Santiago de Chile. We found that plant assemblages of ruderal species were characterised by a higher proportion of alien species (69 taxa), whose original distribution corresponds to the Mediterranean Basin (46 taxa), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…At the global scale, the representation of native and exotic species in urban ecosystems constitutes a phenomenon of increasing attention (Alvey 2006;Aronson et al 2014;McBride 2017). Particularly in south America, several floristic studies in cities show that richness (and abundance) of exotic species-including tree species-exceeds to native ones (Méndez-Stroobandt 2005;Córdova-Stroobandt 2013;Gartner et al 2015;Moro and Castro 2015;Figueroa et al 2016;Santilli et al 2018); these studies also reveal that the richness of exotic species (approx. 60%) exceeds those recorded from North American, Asian, and European cities (50% as average; see Aronson et al 2014).…”
Section: Discussionmentioning
confidence: 93%
“…At the global scale, the representation of native and exotic species in urban ecosystems constitutes a phenomenon of increasing attention (Alvey 2006;Aronson et al 2014;McBride 2017). Particularly in south America, several floristic studies in cities show that richness (and abundance) of exotic species-including tree species-exceeds to native ones (Méndez-Stroobandt 2005;Córdova-Stroobandt 2013;Gartner et al 2015;Moro and Castro 2015;Figueroa et al 2016;Santilli et al 2018); these studies also reveal that the richness of exotic species (approx. 60%) exceeds those recorded from North American, Asian, and European cities (50% as average; see Aronson et al 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Some of these plants were introduced in Chile during the 19th century in botanical gardens due to their different uses, from where they dispersed and became naturalized in the following decades (Gay 1845(Gay -1854. This situation could explain, least partially, the high proportion of wild edible plants in urban areas (Gartner et al 2015). Other potential explanation to the great proportion of edible plants in urban areas is the ability of alien weeds to adapt to harsh conditions (McKinney 2006).…”
Section: Discussionmentioning
confidence: 99%
“…U rban areas are considered novel anthroposystems with distinctive species composition (Hobbs et al 2006, Kowarik 2011) mainly due to the arrival of alien species (Mack & Lonsdale 2001), native species loss (Hahs et al 2009) and stressful abiotic conditions (Bolund & Hunhammar 1999). Flora in urban areas has been widely characterized worldwide showing a high proportion of alien species, as described in cities of Europe (between 19 -40 %, Ricotta et al 2012a, Lososová et al 2016, North America (19 -58 %, Clemants & Moore 2003, Knapp et al 2012, Asia (43 -77 %, Zhao et al 2010, Nagendra & Gopal 2011, Wang et al 2011 and South America (83 -96 %, Gartner et al 2015, Figueroa et al 2016, Fischer et al 2016. Historical records of urban species allow us to trace their native origin and arrival time in the new ranges (Ricotta et al 2012a, Lososová et al 2016, which raise urban floras as suitable models for the understanding of community assembly mechanisms and vegetation succession dynamics (Corlett et al 2002, Termote et al 2012.…”
mentioning
confidence: 99%
“…Fischer et al (2016) analysed the composition of spontaneous weeds in grassland and wooded areas of 15 parks of Santiago and found that exotic species contributed for > 90% to the total diversity. Gärtner et al (2015) conducted a study on the ruderal herbs spontaneously growing in public spaces of Santiago and found that 16% of the taxa were native while 84% were exotic; additionally, Figueroa et al (2018) found that 84% of the taxa present in private and public parks in Santiago were exotic species. Interestingly, by using a systematic sampling for the five studied cities we recorded 302 species of which approx.…”
Section: Discussionmentioning
confidence: 99%